Penerapan Model Waterfall Dalam Pengembangan Sistem Informasi Aset Destinasi Wisata Berbasis Website - Yunus Anis; Artin Bayu Mukti; Azis Nur Rosyid (STMIK Budi Darma, 2023)
The development of this asset information system is aimed at a tourist destination. Candirejo is a village in the Borobudur area that holds a variety of tourism potential and assets that are able to provide interesting education and experiences for tourists. Candirejo Tourism Village is managed by the Candirejo Tourism Village Cooperative (KDWC) which is a legal entity. As village village manager, KDWC also has the duty and responsibility of managing member assets and village assets that are used for the benefit of the village village. Asset inventory in the form of data collection, recording and reporting of physical assets, notes and documents, has not been carried out properly, still relying on books, paper, physical files and recording using software such as spreadsheets and word processors which are commonly used in the office world. The waterfall model is used to develop systems that suit these needs. The stages in the waterfall model have proven capable of producing a website-based tourist destination asset information system in the form of a dashboard for asset management, asset form, asset classification, person in charge and asset profile